Clinical-pathological analysis of squamous cell carcinoma on the oral floor: A case report - Araújo , Jéssica Maria do Nascimento (2021)
Squamous cell carcinoma of the lower lip is one of the most common malignant neoplasms of the oral and maxillofacial region. The aim of the present study was to report a clinical case of squamous cell carcinoma on the oral floor. Female patient, 57 years old, smoker and alcoholic for a period of ten years, attended the dental clinic showing an increase in volume in the region of the oral floor, with painful symptoms, hardened consistency, and duration of 2 years. Under the clinical hypothesis of oral squamous cell carcinoma, an incisional biopsy was performed, which revealed an epithelial malignant neoplasm showing nests and islands of cells with a hyperchromatic nucleus, moderate nuclear and cellular pleomorphism, and keratin pearls. The stroma exhibited a moderate predominantly mononuclear inflammatory infiltrate. Based on the definitive diagnosis of squamous cell carcinoma, the patient was referred to a cancer referral center. The findings of the present case underscore the importance of a correct diagnosis and highlight the importance of a thorough clinical examination, making it necessary to correlate the clinical, radiographic and histopathological data for the correct diagnosis.